Flavivirus-Mediating B Cell Differentiation Into Antibody-Secreting Cells in Humans Is Associated With the Activation of the Tryptophan Metabolism - Bonezi, Vivian; Cataneo, Allan H. D.; Branquinho, Maryana S. F.; Silva, Maysa B. B.; Gonzalez-Dias, Patricia; Pereira, Samuel S.; Ferreira, Luís C. de Souza; Nakaya, Helder I.; Campa, Ana; Wowk, Pryscilla F.; Silveira, Eduardo L. V. (Frontiers in Immunology, 2020)
Patients infected with the Dengue virus (DENV) often present a massive generation of DENV-specific antibody-secreting cells (ASCs) in the blood. In some cases, these ASCs represent more than 50% of the circulating B cells, higher magnitude than those induced by other infections, vaccination, and plasma cell lymphomas. However, it remains unclear how the DENV infection elicits this colossal response. To address this issue, we utilised an in vitro strategy to induce human PBMCs of healthy individuals incubated with DENV particles (DENV4 TVP/360) to differentiate into ASCs. As controls, PBMCs were incubated with a mitogen cocktail or supernatants of uninfected C6/36 cells (mock). The ASC phenotype and function were increasingly detected in the DENV and mitogen cultured PBMCs as compared to mock-treated cells. In contrast to the in vivo condition, secreted IgG derived from the PBMC-DENV culture is not DENV-specific. Lower ASC numbers were observed when inactivated viral particles or purified B cells were added to the cultures. The physical contact was essential between B cells and the remaining PBMCs for the DENV-mediated ASC response. Considering the evidences for the activation of the tryptophan metabolism detected in the serum of Dengue patients, we assessed its relevance in the DENV-mediated ASC differentiation. For this, tryptophan and its respective metabolites were quantified in the supernatants of cell cultures through mass spectrophotometry. Tryptophan depletion and kynurenine accumulation were found in the supernatants of PBMC-DENV cultures, which presented enhanced detection of indoleamine 2,3-dioxygenase 1 and 2 transcripts as compared to controls. In PBMC-DENV cultures, tryptophan and kynurenine levels strongly correlated to the respective ASC numbers, while the kynurenine levels were directly proportional to the secreted IgG titers. Contrastingly, PBMCs incubated with Zika or attenuated Yellow Fever viruses showed no correlation between their kynurenine concentrations and ASC numbers. Therefore, our data revealed the existence of distinct pathways for the DENV-mediated ASC differentiation and suggest the involvement of the tryptophan metabolism in this cellular process triggered by flavivirus infections.